Renewable energy driven heat pumps decarbonization potential in existing residential buildings: Roadmap and case study of Spain. (15th May 2022) - Borge-Diez, David; Icaza, Daniel; Trujillo-Cueva, Diego Francisco; Açıkkalp, Emin
Abstract: Buildings are one of the most important energy consumers worldwide and heating requirements are usually achieved using fossil fuels. This situation poses a risk to achieving the objectives for emissions reduction in existing buildings and electrification, based on heat pumps. It is one of the most feasible solutions to achieve emissions reduction objectives. Current research analyzes the potential for decarbonization of heat pumps and uses the Spanish scenario as a novel case study, where 8.5% of carbon dioxide emissions into the atmosphere came from the residential sector, with 66% of the energy consumption associated with cooling and heating. Using EnergyPlan the potential of decarbonization using heat pumps or heating systems in existing buildings and installing this technology in new buildings is analyzed. Results show a reduction of 8.43% in total emissions and prove that the proposed methodology can be extended worldwide as a solution to reduce emissions and improve energy efficiency in existent heating systems in buildings. Moreover, the integration of electrical climatization systems allows increasing the renewable electricity share in the grid or electrical vehicles integration, among others. Graphical abstract: Image 1 Highlights: Heating in existing buildings using Natural Gas difficult decarbonization . Building heating systems decarbonization poses a risk to achieve 2050 objectives. EnergyPLAN to study potential of heat pumps for heating decarbonization in Spain. Results show 8.43% greenhouse gases reduction and include an implementation roadmap. The methodology and solution can be applied worldwide in existent and new buildings.